Pemanfaatan Penginderaan Jauh Dalam Penilaian Keberhasilan Reklamasi di Lahan Pasca Tambang PT. Vale Indonesia - Nursaputra, Munajat; Larekeng, Siti Halimah; Nasri, Nasri; Hamzah, Andi Siady; Mustari, Andi Subhan; Arif, Abdur Rahman; Ambodo, Aris Prio; Lawang, Yohan; Ardiansyah, Andri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Mining activities with an open system trigger land degradation which results in a decrease in land quality. The decline in land quality is related to the level of fertility and soil chemical properties, so that in general ex-mining land contains low nutrients. These problems in several mining companies that implement environmental sustainability are resolved through reclamation activities. This reclamation activity needs to be assessed, to measure the success of the mine in overcoming land degradation problems. In this study we demonstrate an assessment of the success of mine reclamation in the largest nickel mining area in South Sulawesi, using remote sensing technology. Formulation of NIR and Red bands on Sentinel 2 imagery can produce Normalized Difference Vegetation Index index. From the vegetation index value, it is known that the observed reclamation area is close to the high vegetation index value (0.7 - 0.9). This value is actually close to the vegetation index value in the surrounding natural forest, but with a low percentage of area. The distribution of the results of the assessment of plant growth in the reclamation area was lowest vegetation by 3.14%; lower vegetation by 12.15%; low vegetation by 21.53%; moderate vegetation by 14.82%; high vegetation by 25.94% and higher vegetation by 22.42% of the total reclamation area.